2019
DOI: 10.1080/02699052.2019.1643921
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep deficiency in the trajectory of postconcussive symptoms in adolescents

Abstract: Objective: To investigate the trajectory of sleep deficiency after concussion and examine its role as a predictor of postconcussive symptoms (PCS) over 3 weeks and at 3 months post-concussion. Design: This was a prospective pilot study of 29 adolescents recruited from a pediatric Emergency Department (69% female, mean age = 14.0 years, SD = 1.8) following a concussion. Methods: Adolescents completed questionnaire assessments at baseline, Weeks 1, 2, and 3 on PCS and sleep patterns. Concurrently, adolescents al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…Weekday and weekend nights were included in our actigraph calculations, which may have altered the findings given that youth tend to differ in their weekday and weekend sleep patterns. [42] However, it is consistent with previous pediatric research [26][27][28][29] and does allow for a more comprehensive estimate of the amount of sleep deprivation and disruption experienced throughout the week. Also, the current study assessed HCU using retrospective guardian report, which may be influenced by response bias.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Weekday and weekend nights were included in our actigraph calculations, which may have altered the findings given that youth tend to differ in their weekday and weekend sleep patterns. [42] However, it is consistent with previous pediatric research [26][27][28][29] and does allow for a more comprehensive estimate of the amount of sleep deprivation and disruption experienced throughout the week. Also, the current study assessed HCU using retrospective guardian report, which may be influenced by response bias.…”
Section: Discussionsupporting
confidence: 82%
“…This takes into account variability in sleep during the week that may be important for understanding the general level of sleep deprivation and disruption experienced by youth with SCD, and is consistent with previous pediatric research studies. [26][27][28][29] Sleep actigraphy has been validated in comparison to polysomnography, with agreement rates for sleep and wake identification higher than 90%. [30]…”
Section: Sleep Duration and Sleepmentioning
confidence: 99%
“…Two studies evaluating sleep after pediatric concussion found poor sleep quality to be strongly associated with greater concussion symptom severity and longer recovery times following SRC. 38,42 Similarly, a study looking at collegiate athletes found daytime sleepiness and insomnia to be a risk factor for SRC, 43 further highlighting the need for sleep to be assessed and incorporated into treatment recommendations to ensure safe return to sport participation. Emphasizing the importance of proper sleep hygiene can improve these sleep disturbances.…”
Section: Symptom Assessmentmentioning
confidence: 99%
“…Over the first 3 weeks, sleep duration and daytime sleepiness gradually declined; however, insomnia symptoms remain unchanged. 71 Piantino et al proposed a model where changes in the lymphatic function caused by TBI and posttraumatic sleep disruption may impair the clearance of neuropeptides involved in the pathogenesis of posttraumatic headaches and posttraumatic sleep. 72 Not only are sleep disturbances associated with fatigue and reduced quality of life in the acute phase, but they may hinder recovery from other concussion symptoms, 73,74 often with exacerbation of problems such as headache and cognitive deficits.…”
Section: Sleepmentioning
confidence: 99%